Mobile E-Learning Mata Pelajaran Natural Sciences (IPA) Berbasis User Centered Design - Olha Musa; Abdul Malik I Buna; Yulanda Yunus; Zainudin Sidik (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
In this study, designing a system based on mobile e-learning which is a necessity for formal educational institutions in the era of globalization which is increasingly inevitable. Systematically implement a program of guidance, teaching, based on observations and interviews with one of the science subject teachers at MTs Al-Khairaat Kwandang that the learning process, especially about the excretory system, is still explanatory without any teaching aids where students can see the organs included in the excretory system. . The purpose of this study is to create a mobile e-learning system about science subjects for class VIII 3 at MTs Al-Khairaat Kwandang that is easy to use by students and teachers. The method used is the UCD method. This application is designed using PHP and HTML programming language software, namely Sublime, Java Programming Language Using Android Studio, and modeling tools using UML (Unified Modeling Language). The results of this system research use whitebox and blackbox where with this test the correct graph flow is obtained as a sample, the researchers conduct tests on the flowchart in the evaluation. The conclusion obtained: Region (R) = 4 Independent Paths (Independent path) = 4 Cyclometic Complexity (CC) = 4 provided that this research can be implemented